2013
DOI: 10.1016/j.biomaterials.2013.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and immunotoxicity of silver nanoparticles in an intravenous 28 days repeated dose toxicity study in rats

Abstract: Because of its antibacterial activity nanosilver is one of the most commonly used nanomaterials. It is increasingly used in a variety of both medical and consumer products resulting in an increase in human exposure. However, the knowledge on the systemic toxicity of nanosilver is relatively limited. To determine the potential systemic toxicity of silver nanoparticles (Ag-NP) with different sizes (20 nm and 100 nm) a 28-days repeated dose toxicity study was performed in rats using intravenous administration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
186
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(200 citation statements)
references
References 21 publications
9
186
1
4
Order By: Relevance
“…The De Jong et al (2013) study, a 28-day study in rats investigating a series of immunotoxicological endpoints after exposure to 20 nm AgNP, qualified to serve as the critical study for the pTI derivation. De Jong et al (2013) reported the lowest dose-dependent critical health effect, which was a BMDL05 of 0.14 mg/kg bw/day for increased spleen weight. To derive the pTI, a modifying factor (MF) of 1,000 was applied to the POD to account for interindividual variability (10), potential interspecies difference in potency (10), and the lack of chronic toxicity study data (10) based on scientific review.…”
Section: Resultsmentioning
confidence: 99%
“…The De Jong et al (2013) study, a 28-day study in rats investigating a series of immunotoxicological endpoints after exposure to 20 nm AgNP, qualified to serve as the critical study for the pTI derivation. De Jong et al (2013) reported the lowest dose-dependent critical health effect, which was a BMDL05 of 0.14 mg/kg bw/day for increased spleen weight. To derive the pTI, a modifying factor (MF) of 1,000 was applied to the POD to account for interindividual variability (10), potential interspecies difference in potency (10), and the lack of chronic toxicity study data (10) based on scientific review.…”
Section: Resultsmentioning
confidence: 99%
“…14 The intravenous administration of AgNPs also showed immunotoxicity in murine models. 15 Respiratory tract immune toxicity has also been associated with AgNPs. 16 AgNP treatment of peripheral blood mononuclear cells and human mesenchymal stem cells showed inhibition of the production of cytokines, such as IFN-c, IL-6, IL-8, IL-11, TNF-a and more weakly, IL-5.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other in vitro studies showed that cytokine production in macrophages can be induced by nanosilver (Martinez-Gutierrez et al 2012)(Also, human peripheral blood mononuclear cells produced IL-6 and IL8 after exposure to Ag-NP, whereas TNFα production was not affected In contrast, in an intravenous 28-day repeated dose toxicity study in rats with 20 nm and 100 nm nanosilver, no cytokine level changes were found -although ex vivo cytokine induction and production by isolated spleen cells were affected (De Jong et al 2013). In this study, Wistar rats were treated with a maximum dose of 6 mg/kg body weight, which was well tolerated by the animals.…”
Section: Immune Responses and Allergiesmentioning
confidence: 99%